Adubos verdes irrigados com efluente tratado de laticínio e cultivo em sucessão da alface e beterraba em consórcio - Vizú, Juliana de Fátima (2018)
The objective of this work is to verify the development of green manure and its influence on the chemical characteristics of the soil and the cultivation in succession of the lettuce (Lactuca sativa L.) consortium, and beet (Beta vulgaris L.), with the contribution of treated effluent of dairy. The experimental design used for the randomized blocks, in a factorial scheme (2 x 5) with two water sources (treated effluent of dairy) and four green manures Crotalaria juncea, Crotalaria spectabilis, Cajanus cajan, Canavalia ensiformes and (control green fertilizer), with four replicates. In the 70 days after sowing, it analyzed the green manures and the soil, and transplanted to the lettuce and beet seedlings. In the 45 days after the transplant, they were analyzed as lettuce plants in 73 days as beet plants. Pork bean was the only green manure that yielded similar productivity when irrigated with both sources of water, and the others had a smaller phytomass when irrigated with treated dairy effluent. Phytoextraction was low by green manures. There was an increase in sodium concentration in the soil irrigated with treated dairy effluent. The contribution of effluent did not influence the nodulation of the green manures, but contributed to soil chemical fertility, with increase of phosphorus, calcium and magnesium. As lettuce and beet plants produced satisfactorily with an irrigation with treated effluent of dairy in succession to the cultivation of green fertilizers